A cross-sectional study of Jamaican adolescents' risk for type 2 diabetes and cardiovascular diseases. Issue 7 (11th July 2013) - Barrett, Sheila C; Huffman, Fatma G; Johnson, Paulette; Campa, Adriana; Magnus, Marcia; Ragoobirsingh, Dalip
Abstract : Objectives: To compare obese versus non-obese Jamaican adolescents' risk for type 2 diabetes (T2D) and cardiovascular diseases (CVDs); and to explore a suitable and economical method of screening for these risk factors in the school settings. Design: A descriptive cross-sectional study of adolescents' risk for T2D and CVD. All the participants were examined at their respective schools. Setting: Jamaica, West Indies. Population: 276 Jamaican adolescents aged 14–19 years, randomly selected from grades 9 to 12 from 10 high schools on the island and included both boys and girls. All ethnicities on the island were represented. Main outcome measures: High fasting blood glucose, total cholesterol, glycated haemoglobin (HbA1c), blood pressure, body mass index (BMI), waist circumference, waist-to-hip ratio, family history of obesity, T2D and CVDs, low physical activity, and presence of Acanthosis Nigricans. All blood measures were analysed using the finger prick procedure. Results: Waist circumference, waist-to-hip ratio, Acanthosis Nigricans, total cholesterol, family history of T2D and blood pressure were the strongest predictors of BMI (p=0.001). Over one-third of the participants were overweight. Jamaican adolescent females had a significantly higher number of risk factors and were less physically active than males (p<0.05). Over 80% of participants reported ≥3 risk factors for T2D and CVD. Participants with BMI ≥25 reported five or more risk factors. One-third of the overweight participants were classified with metabolic syndrome. Conclusions: Jamaican adolescents are at risk of T2D and CVD. Family history of disease and anthropometric measures identified more participants at risk than did the blood measures. Jamaican adolescent females reported more risk factors for T2D and CVD as compared to males. Collection of this type of data was feasible within the school settings. All data were collected in 1 day per school. Intervention measures are needed to educate Jamaican adolescents to reduce overweight and subsequently the risk factors.